2023
DOI: 10.1177/10711007231205289
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Fifth Metatarsal Osteotomy for Bunionette Deformity Without Fixation or Strapping: A Retrospective Study

Akram Al Ramlawi,
Dev Paul Patel,
Beth G. Ashinsky
et al.

Abstract: Background: Bunionette deformity (BD) is a painful condition of the fifth metatarsal characterized by an osseous prominence and fifth toe varus deformity. The purpose of this study is to assess the clinical, functional, and radiographic outcomes of percutaneous distal metatarsal metaphyseal osteotomy (DMMO) without fixation or postoperative strapping of the foot. Methods: A retrospective case series was performed on 111 patients (132 feet) with symptomatic BD who underwent percutaneous DMMO of the fifth metata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The study reported that the functional therapy resulted in excellent clinical outcomes after an average follow-up of 22 months, with no significant differences based on the type of fracture. 38 This approach aligns with the findings of, 39 who suggested that athletes with fifth metatarsal fractures may benefit from surgical screw fixation, leading to optimal healing within approximately 7 to 12 weeks after surgery. However, Baumbach et al demonstrated that functional treatment without stabilization also yielded positive outcomes, emphasizing early return to activities and sports.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The study reported that the functional therapy resulted in excellent clinical outcomes after an average follow-up of 22 months, with no significant differences based on the type of fracture. 38 This approach aligns with the findings of, 39 who suggested that athletes with fifth metatarsal fractures may benefit from surgical screw fixation, leading to optimal healing within approximately 7 to 12 weeks after surgery. However, Baumbach et al demonstrated that functional treatment without stabilization also yielded positive outcomes, emphasizing early return to activities and sports.…”
Section: Discussionsupporting
confidence: 77%
“…However, Baumbach et al demonstrated that functional treatment without stabilization also yielded positive outcomes, emphasizing early return to activities and sports. 38 Furthermore, Chu et al 3 highlighted the importance of a conservative approach, including rehabilitative exercises and various therapies, in the nonoperative management of fifth metatarsal fractures. This aligns with the functional treatment approach employed by Baumbach et al, where patients were not subjected to any form of stabilization but were encouraged to resume activities early, resulting in successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complications observed were irritation from K-wires in fixed osteotomies 14 , 20 , 33 or hypertrophic callus in unfixed osteotomies. 1 , 9 - 11 , 25 , 28 , 32 The hypertrophic callus is likely due to the residual instability of nonfixed osteotomies and can be easily treated if symptomatic. 28 Interestingly, 3 studies 16 , 25 , 32 reported that this callus resolved without surgical intervention over time, which is a phenomenon observed by the authors of this study as shown in Figure 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of FAI, Al Ramwali et al assess the results of a percutaneous technique, the minimally invasive distal metatarsal osteotomy of the 5th ray (DMMO 5) to treat bunionette. 1 They report excellent results in a fairly large series, with very few complications (1.5%), which can be considered minor. The postoperative period is that of a percutaneous procedure without fixation, with the wearing of a flat postoperative shoe for a few weeks, before resuming comfortable footwear around the 6th week, and physical activities after 3 months.…”
mentioning
confidence: 91%
“…In this issue of FAI, Al Ramwali et al assess the results of a percutaneous technique, the minimally invasive distal metatarsal osteotomy of the 5th ray (DMMO 5) to treat bunionette. 1…”
mentioning
confidence: 99%